2019
DOI: 10.1088/1742-6596/1321/2/022041
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of condition extraction in quantification of total flavonoid content in the seeds of the Arummanis (Mangifera indica L.) mango from Indonesia

Abstract: Mangoes are an abundant local fruit. Mango seed is a biowaste material that only becomes an environmental problem. Therefore, a study was conducted to utilize one of the compounds contained in mango seeds particularly the seeds of the Arummanis (Mangifera indica L.) from Indonesia, namely flavonoids. One of the most optimum methods is used for extraction with a variety of solvents, namely ethanol, methanol, and hexane. Determination of total flavonoid content is based on the AlCl3 method with total flavonoids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…This is because ethanol is superior to water and methanol regarding its traceability. According to Masturi et al, [24], the optimal total flavonoid content of harumanis seeds was obtained using a 96% ethanol solvent. Thus, it can be concluded that organic solvents derived from water, such as 50% ethanol and 50% methanol, were notably effective at extracting the flavonoid content of harumanis leaves.…”
Section: Total Phenolic and Flavonoid Contents Of Harumanis Leaves Ex...mentioning
confidence: 99%
“…This is because ethanol is superior to water and methanol regarding its traceability. According to Masturi et al, [24], the optimal total flavonoid content of harumanis seeds was obtained using a 96% ethanol solvent. Thus, it can be concluded that organic solvents derived from water, such as 50% ethanol and 50% methanol, were notably effective at extracting the flavonoid content of harumanis leaves.…”
Section: Total Phenolic and Flavonoid Contents Of Harumanis Leaves Ex...mentioning
confidence: 99%
“…The content of flavonoids in mulberry was determined by the AlCl 3 chromogenic method [27]. First, a 0.2 g mulberry sample was accurately weighed by an analytical balance, and 5.0 mL 70% C 2 H 5 OH was added according to a material to liquid ratio of 1:25, and placed into a centrifuge tube.…”
Section: Content Of Functional Componentsmentioning
confidence: 99%
“…Total kandungan flavonoid sampel kemudian ditentukan berdasarkan ekuivalen dengan kurva standar kuersetin. Kuersetin digunakan sebagai standar karena termasuk golongan flavonoid dari gugus flavonol yang memiliki gugus keto pada C-4 dan memiliki gugus hidroksil pada atom C-3 atau C-5 yang berdekatan dari flavon dan flavonol (Matsuri et al, 2019). Berdasarkan Tabel 3, total kandungan flavonoid pada penelitian tertinggi yaitu Xylaria sp.…”
Section: Kandungan Total Flavonoid Cendawan Xylaria Spunclassified